A systematic review of the true benefit of robotic surgery: Ergonomics. Issue 4 (6th May 2020) - Wee, Ian Jun Yan; Kuo, Li‐Jen; Ngu, James Chi‐Yong
Abstract: Background: Ergonomics, as defined by the optimization of one's physical environment to enhance work performance, is an important consideration in surgery. While there have been reviews on the ergonomics of laparoscopy, this has not been the case for robotic surgery despite the rising number of publications. Methods: This study was performed in accordance to the Preferred Reporting Items for Systematic reviews and Meta‐Analyses (PRISMA) guidelines. A search was performed on main databases to identify relevant articles. Results: Twenty‐nine articles were included, comprising 3074 participants. Studies employing objective measurement tools showed that robotics conferred superior ergonomic benefits and reduced work load compared to laparoscopy, for both surgeons and trainees. Survey studies also demonstrated that self‐reported discomfort was lower in robotic procedures compared to laparoscopy and open surgery. Compared to other subspecialities, gynecological procedures seem to be associated with greater surgeon‐reported strain. Conclusion: Robotic surgery is ergonomically superior to open and laparoscopic surgery. However, rates of physical strain remain significant and should be addressed by formal ergonomic training and adequate console familiarization.